Phage types of Salmonella typhi isolated in Malaysia over the 10-year period 1970-1979. - Jegathesan, M. (Cambridge University Press, 1983)
The pattern of phage types of 2553 strains of Salmonella typhi isolated over the 10-year period 1970-9 was studied. During the period 29 different phage types were encountered, not including the categories of 'untypable strains', 'degraded Vi-strains' and Vi negative strains. For the period as a whole, the commonest phage types encountered were A (20.9%), E1 (14.8%), D1 (10.3%), degraded Vi positive strains (10.3%), untypable Vi strains (7.3%), C4 (7.1%), D2 (4.4%), E2 (3.9%) and type 25 (2.6%). There were phage types which appeared in the early years of the period and then disappeared (types B2, D9 and D1-N). Others only made their appearance in recent years (K1 and 53). Notable differences were also seen in the predilection of some phage types for certain geographical areas.